A highly selective ratiometric fluorescent probe for the cascade detection of Zn2+ and H2PO4− and its application in living cell imaging. Issue 64 (21st August 2017) - Du, Kui; Niu, Shizhen; Qiao, Li; Dou, Yandong; Zhu, Qing; Chen, Xinzhi; Zhang, Pengfei
Abstract : A simple ratiometric sensor (L1 ) for the cascade detection of Zn 2+ and H2 PO4 − with high selectivity was reported based on the intermolecular charge transfer (ICT) mechanism. Abstract : A simple ratiometric sensor (L1 ) for the cascade detection of Zn 2+ and H2 PO4 − with high selectivity was reported based on the intermolecular charge transfer (ICT) mechanism. This new sensor could distinguish Zn 2+ from Cd 2+, and features high fluorescence quantum yield withL1 (0.45) andL1 –Zn 2+ (0.27). There is a good linear relationship between the fluorescence ratio I 525 nm / I 430 nm upon addition of Zn 2+ and the limit of detection (LOD) was evaluated to be 41.0 nM. Furthermore, the in situ preparedL1 –Zn 2+ complex also displayed good selectivity and ratiometric response for H2 PO4 − and the detection limit ofL1 –Zn 2+ was found to be 49.0 nM.L1 exhibits permeability and can been applied to the detection of intracellular Zn 2+ and H2 PO4 − in HepG-2 cells.